Sex Differences in Neurotoxicogenetics - Torres-Rojas, Carolina; Jones, Byron C. (Frontiers in Genetics, 2018)
A major development in biomedical research is the recognition that the sex of an individual plays a key role in susceptibility, treatment, and outcomes of most diseases. In this contribution, we present evidence that sex is also important in the toxicity of many environmental toxicants and contributes to the effect of genetics. Thus, individual differences in response to toxicants includes genetic makeup, the environment and sex; in fact, sex differences may be considered a part of genetic constitution. In this review, we present evidence for sex contribution to susceptibility for a number of toxicants.